Resin composition and use thereof

The resin composition, comprising epoxy resin, surface-treated aluminum nitride, and alumina fillers, addresses the challenges of flowability, thermal conductivity, and linear expansion in multilayer printed wiring boards and substrates, enhancing their performance and reliability.

JP2025049964APending Publication Date: 2025-04-04TOKUYAMA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023158504
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing resin compositions for multilayer printed wiring boards and substrates with built-in parts face challenges in achieving high flowability and thermal conductivity while maintaining low linear expansion coefficients.

Method used

A resin composition comprising (A) an epoxy resin, (B) surface-treated aluminum nitride filler, and (C) surface-treated alumina filler, with specific particle size and surface area ratios, which enhances flowability and thermal conductivity while reducing linear expansion.

Benefits of technology

The resin composition achieves excellent flowability, thermal conductivity, and linear expansion properties, improving the reliability and performance of multilayer printed wiring boards and substrates with built-in parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025049964000001
    Figure 2025049964000001
  • Figure 2025049964000002
    Figure 2025049964000002
  • Figure 2025049964000003
    Figure 2025049964000003
Patent Text Reader

Abstract

To provide a resin composition having excellent flowability and having excellent thermal conductivity and linear expansion properties of its cured product.SOLUTION: The resin composition comprises (A) an epoxy resin, (B) an aluminum nitride filler, and (C) an alumina filler. The total amount of the aluminum nitride filler (B) and the alumina filler (C) is 800 to 1800 pts. mass relative to 100 pts. mass of the epoxy resin (A). The epoxy resin (A) comprises (A-1) a solid epoxy resin and (A-2) a liquid epoxy resin. The aluminum nitride filler (B) is a surface-treated aluminum nitride filler that is surface-treated with a silane coupling agent (SC1) having a (meth)acrylic group. The alumina filler (C) is a surface-treated alumina filler that is obtained by surface-treating an alumina filler (C0) having a product of average particle diameter (D50) and specific surface area (SA) of 2.6 or more, with a silane coupling agent (SC2) having an amino group with a secondary amine structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and its use. [Background technology]

[0002] As electronic devices become more compact and perform better, the wiring in multilayer printed wiring boards becomes finer and denser. A known manufacturing technique for multilayer printed wiring boards is a build-up method in which insulating layers and conductor layers are alternately stacked. By using a film-like resin composition (resin composition film) for the insulating layer, the insulating layer can be efficiently formed. As the resin composition film, a resin composition containing a thermosetting epoxy resin and silica is generally used (Patent Document 1). The insulating layer is generally formed by overlapping the resin composition film on the conductor layer, and thermally curing the resin composition while adhering the conductor layer and the resin composition using a vacuum laminator or a heat press.

[0003] For this reason, the resin composition film is required to have high fluidity under lamination conditions in order to conform to the shape of the conductor layer, and it is common to use a combination of a solid epoxy resin and a liquid epoxy resin as the epoxy resin. In addition, since the thermal linear expansion coefficient of the insulating layer and the conductor layer (copper wiring) is significantly different, there is a reliability issue in multilayer printed wiring boards, for example, cracks occurring during thermal cycling, and the insulating layer is also required to have low linear expansion. Therefore, in order to reduce the linear expansion coefficient of the insulating layer, the resin composition film is generally highly filled with silica.

[0004] As a method for high-density mounting, electronic component embedded board technology, in which electronic components that have been mounted on the surface of a board are embedded inside the board with an encapsulating resin, is also attracting attention. A cavity is formed in the core of a resin board and a copper board, electronic components such as ICs and capacitors are placed in the cavity, and then a thermosetting resin is embedded in the cavity, thereby encapsulating and embedding the electronic components. The encapsulating resin can also be a resin composition film as used in the multilayer printed wiring board. The resin composition film is superimposed on the core on which the electronic components are placed, the resin composition is embedded in the cavity by a heat press, and the resin composition is thermally cured to encapsulate (semi-additive method). Even when a resin composition is used for a board with embedded components, the resin composition is required to have high fluidity in order to encapsulate the cavity, and the cured product of the resin composition is required to have low linear expansion.

[0005] As a higher density mounting form, a module is also used in which a multilayer wiring layer is formed by the semi-additive method on the surface of a component-embedded substrate having electronic components built into the substrate, and further electronic components are mounted on the surface.

[0006] Furthermore, in recent years, as electronic devices become smaller and more powerful, the density and packaging of semiconductor elements in multilayer printed wiring boards and component-embedded boards is increasing. This is accompanied by an increase in the amount of heat generated by the semiconductor elements, making it important to efficiently dissipate that heat from the board. In order to address these issues, it has been proposed to use a high thermal conductivity resin composition that uses aluminum nitride, which has a higher thermal conductivity than silica, as a resin composition film in the manufacture of multilayer printed wiring boards using the build-up method (Patent Document 2). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2011-132507 A [Patent Document 2] International Publication No. 2014 / 208352 Summary of the Invention [Problem to be solved by the invention]

[0008] Resin composition films used in multilayer printed wiring boards and component-embedded substrates are desired to have high fluidity, and cured products made from the resin composition films are desired to have high thermal conductivity. However, when the filling rate of the filler in the resin composition is increased in order to improve the thermal conductivity of the cured product, the flowability of the resin composition may decrease. Therefore, an object of the present invention is to provide a resin composition which has excellent flowability and, when cured, has excellent thermal conductivity and linear expansion properties. [Means for solving the problem]

[0009] The resin composition of the present invention relates to, for example, the following items [1] to [9]. [1] (A) an epoxy resin, (B) an aluminum nitride filler, and (C) an alumina filler; The (B) aluminum nitride filler and the (C) alumina filler are contained in a total amount of 800 to 1800 parts by mass relative to 100 parts by mass of the (A) epoxy resin, The (A) epoxy resin comprises (A-1) a solid epoxy resin and (A-2) a liquid epoxy resin, the aluminum nitride filler (B) is a surface-treated aluminum nitride filler that has been surface-treated with a silane coupling agent (SC1) having an organic reactive group including a (meth)acrylic group, The (C) alumina filler has an average particle size D50 (μm) and a specific surface area SA (m 2the (C0) alumina filler having a product (R / g) of 2.6 or more is a surface-treated alumina filler that has been surface-treated with a silane coupling agent (SC2) having an organic reactive group containing an amino group of a secondary amine structure, which is different from the organic reactive group possessed by the silane coupling agent (SC1); and the (B) aluminum nitride filler has an average particle size D50 larger than the average particle size D50 of the (C) alumina filler. Resin composition.

[0010] [2] In the (C0) alumina filler, the average particle size D50 (μm) and the crystallite size L calculated from the half-width of the diffraction peak due to the (104) plane obtained by X-ray diffraction measurement 104 (μm) ratio (D50 / L 104 ) is 6.0 or higher, The resin composition according to [1].

[0011] [3] In the (C0) alumina filler, the ratio (D90 / D10) of the 90% particle diameter D90 to the 10% particle diameter D10 calculated from the volume-based cumulative particle size distribution is 2.3 or less. The resin composition according to [1] or [2].

[0012] [4] The silane coupling agent (SC2) has an organic reactive group containing a phenylamino group. The resin composition according to any one of [1] to [3].

[0013] [5] The (B) aluminum nitride filler has an average particle size D50 of 0.2 to 3 μm and a maximum particle size Dmax of 5 μm or less, The average particle size D50 of the (C) alumina filler is 0.05 to 1.5 μm. The resin composition according to any one of [1] to [4].

[0014] [6] The specific surface area SA of the aluminum nitride filler (B) is 0.5 to 10 m 2 / g, The specific surface area SA of the alumina filler (C) is 1 to 50 m 2 / g, The resin composition according to any one of [1] to [5].

[0015] [7] A resin composition film comprising the resin composition according to any one of [1] to [6].

[0016] [8] A multilayer printed wiring board comprising the resin composition according to any one of [1] to [6] or a cured product thereof.

[0017] [9] A component-embedded substrate comprising the resin composition according to any one of [1] to [6] or a cured product thereof. Effect of the Invention

[0018] According to the present invention, it is possible to provide a resin composition which is excellent in flowability and which, in addition, exhibits excellent thermal conductivity and linear expansion properties when cured. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] An example of an embodiment of the present invention will be described in detail below. However, the present invention is not limited to the embodiment described below, and can be modified as desired without departing from the gist of the present invention. In this specification, "(meth)acrylic" refers to both or either of "acrylic" and "methacrylic".

[0020] [(A) Epoxy resin] The resin composition of the present invention contains an epoxy resin (A). The epoxy resin (A) preferably contains a compound containing one or more epoxy groups in the molecule (hereinafter, sometimes referred to as a "reactive epoxy resin"). The reactive epoxy resin may be a low molecular weight compound having an epoxy group. The reactive epoxy resin more preferably contains two or more epoxy groups in the molecule.

[0021] The (A) epoxy resin preferably contains 50% by mass or more of a reactive epoxy resin based on the total amount of the (A) epoxy resin. When the (A) epoxy resin contains a reactive epoxy resin, the resin composition tends to soften and have excellent fluidity. Therefore, when the resin composition is used as a resin composition film for producing a multilayer printed wiring board or a component-embedded substrate, the resin composition is likely to conform to the shape of the conductor layer of the multilayer printed wiring board, the cavity of the component-embedded substrate, and the shape of the electronic component. In addition, the resin composition is changed into a desired shape and then heat-cured to produce a cured product with high strength and heat resistance, thereby improving the reliability of the substrate, etc. There is no particular upper limit for the content of the reactive epoxy resin in the total amount of the epoxy resin (A), and all of the epoxy resin (A) may be a reactive epoxy resin.

[0022] The epoxy resin (A) includes a solid epoxy resin (A-1) and a liquid epoxy resin (A-2). In this specification, an epoxy resin that is solid at a temperature of 25° C. is referred to as a solid epoxy resin (A-1), and an epoxy resin that is liquid at 25° C. is referred to as a liquid epoxy resin (A-2).

[0023] When the epoxy resin (A) contains the solid epoxy resin (A-1), the strength and heat resistance of the cured product obtained by thermally curing the resin composition tends to be improved. On the other hand, since the melt viscosity of the solid epoxy resin (A-1) tends to be high, the fluidity of the resin composition is improved by using the highly heat-resistant solid epoxy resin (A-1) in combination with the highly fluid liquid epoxy resin (A-2), and the resin composition can conform to the desired substrate shape.

[0024] The (A-1) solid epoxy resin is preferably a reactive epoxy resin. As the (A-1) solid epoxy resin, tetrafunctional naphthalene type epoxy resin, trifunctional naphthalene type epoxy resin, trisphenolmethane type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A novolac type epoxy resin, naphthol novolac type epoxy resin, naphthol cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, biphenyl aralkyl type epoxy resin, bixylenol type epoxy resin, naphthylene ether type epoxy resin, biphenyl type epoxy resin and fluorene type epoxy resin are preferred, and tetrafunctional naphthalene type epoxy resin, biphenyl aralkyl type epoxy resin, trisphenolmethane type epoxy resin, bixylenol type epoxy resin, naphthylene ether type epoxy resin and fluorene type epoxy resin are more preferred.

[0025] Examples of tetrafunctional naphthalene type epoxy resins include "HP-4700" and "HP-4710" manufactured by DIC Corporation. Examples of cresol novolac type epoxy resins include "N-690" and "N-695" manufactured by DIC Corporation.

[0026] Examples of dicyclopentadiene type epoxy resins include "HP-7200," "HP-7200L," and "HP-7200H" manufactured by DIC Corporation. Examples of naphthylene ether type epoxy resins include "HP6000" and "HP-6000H" manufactured by DIC Corporation.

[0027] Examples of trisphenolmethane type epoxy resins include "EPPN-501H", "EPPN-501HY" and "EPPN-502H" manufactured by Nippon Kayaku Co., Ltd. Examples of naphthol cresol novolac epoxy resins include "NC7000L", "NC-7000H" and "NC-7300L" manufactured by Nippon Kayaku Co., Ltd. Examples of biphenylaralkyl type epoxy resins include "NC-3000H", "NC-3000", "NC-3000L", "NC-3100" and "NC-3500" manufactured by Nippon Kayaku Co., Ltd.

[0028] Examples of naphthol novolac type epoxy resins include "ESN475" and "ESN485" manufactured by Nippon Steel Chemical Co., Ltd. Examples of biphenyl type epoxy resins include "YX4000H" and "YL6121" manufactured by Mitsubishi Chemical Corporation. An example of the bixylenol type epoxy resin is "YX4000HK" manufactured by Mitsubishi Chemical Corporation. An example of the fluorene type epoxy resin is "YL7800" manufactured by Mitsubishi Chemical Corporation.

[0029] The softening point of the solid epoxy resin (A-1) is preferably 40 to 130°C, more preferably 45 to 110°C, and even more preferably 50 to 100°C, from the viewpoint of moldability of the resin composition. The solid epoxy resin (A-1) may be used alone or in combination of two or more kinds.

[0030] The (A-1) solid epoxy resin may be used as a composition containing the (A-1) solid epoxy resin and an organic solvent when producing the resin composition. The organic solvent in the composition may be any solvent capable of dissolving the solid epoxy resin (A-1), and examples thereof include acetone, methanol, ethanol, butanol, 2-propanol, 2-methoxyethanol, 2-ethoxyethanol, 1-methoxy-2-propanol, 2-acetoxy-1-methoxypropane, toluene, xylene, methyl ethyl ketone, N,N-dimethylformamide, methyl isobutyl ketone, N-methyl-pyrrolidone, n-hexane, cyclohexane, cyclohexanone, and solvent naphtha, which is a mixture thereof, and preferably methyl ethyl ketone. The boiling point of the organic solvent is preferably 200° C. or lower, more preferably 180° C. or lower, from the viewpoint of ease of removal of the organic solvent. The organic solvent may be used alone or in combination of two or more kinds.

[0031] The content of nonvolatile matter in the composition is preferably 20 to 90 mass %, more preferably 30 to 80 mass %, and even more preferably 40 to 70 mass %, from the viewpoint of solubility of the solid epoxy resin (A-1) in an organic solvent. In this specification, non-volatile content refers to all components excluding the solvent. The content of the organic solvent in the composition is preferably 10 to 80% by mass, more preferably 20 to 70% by mass, and further preferably 30 to 60% by mass. The composition may contain components other than the (A) epoxy resin, (B) aluminum nitride filler, and (C) alumina filler that the resin composition may contain.

[0032] When the epoxy resin (A) contains the liquid epoxy resin (A-2), the resin composition tends to have excellent fluidity, and therefore, when a film made of the resin composition is molded under heat and pressure for use in a multilayer printed wiring board and a component-embedded board, the film made of the resin composition has excellent conformability to the shapes of a conductor layer and a cavity.

[0033] (A-2) The liquid epoxy resin is preferably a reactive epoxy resin. As the (A-2) liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, phenol novolac type epoxy resin and naphthalene type epoxy resin are preferred, and bisphenol A type epoxy resin and bisphenol F type epoxy resin are more preferred.

[0034] Examples of bisphenol A type epoxy resins include "jER828", "jER828EL" and "jER828US" manufactured by Mitsubishi Chemical Corporation. Examples of bisphenol F type epoxy resins include "jER806", "jER806H" and "jER807" manufactured by Mitsubishi Chemical Corporation, and "YDF-8170C" manufactured by Nippon Steel Chemical & Material Corporation. An example of the phenol novolac type epoxy resin is "jER152" manufactured by Mitsubishi Chemical Corporation.

[0035] An example of a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin is "ZX1059" manufactured by Nippon Steel Chemical & Material Corporation. Examples of naphthalene-type epoxy resins include "HP4032," "HP4032D," and "HP4032SS" manufactured by DIC Corporation. The (A-2) liquid epoxy resin may be used alone or in combination of two or more kinds.

[0036] The viscosity of the liquid epoxy resin (A-2) at 25° C. is preferably 500 poise or less, more preferably 5 to 300 poise, and even more preferably 10 to 200 poise. When the viscosity of the (A-2) liquid epoxy resin at 25° C. is within the above range, the melt viscosity of the resin composition can be kept low, and the resin composition tends to have excellent flowability.

[0037] The ratio of the contents of the solid epoxy resin (A-1) and the liquid epoxy resin (A-2) (solid epoxy resin:liquid epoxy resin) is preferably in the range of 9:1 to 1:9, more preferably 4:1 to 1:4, further preferably 3:1 to 1:3, and particularly preferably 2:1 to 1:2. By setting the ratio of the contents of the solid epoxy resin (A-1) and the liquid epoxy resin (A-2) within the above range, it is possible to achieve both high fluidity of the resin composition and high heat resistance of the cured product.

[0038] The epoxy equivalent of the (A) epoxy resin is preferably 50 to 4500, more preferably 50 to 3000, further preferably 80 to 2000, and particularly preferably 100 to 1000. When the epoxy equivalent of the (A) epoxy resin is within the above range, the cured product obtained by curing the resin composition tends to have excellent crosslink density, and when the resin composition is used as a film, it tends to have sufficient heat resistance and mechanical strength. The epoxy equivalent can be measured according to JIS K 7236. The epoxy equivalent is the mass of resin per equivalent of epoxy groups.

[0039] [(B) Aluminum nitride filler] The resin composition contains (B) an aluminum nitride filler. (B) The aluminum nitride filler is an aluminum nitride filler that has been surface-treated with a silane coupling agent (SC1) having an organic reactive group including a (meth)acrylic group. The aluminum nitride filler that has been surface-treated with the silane coupling agent (SC1) is also called a "surface-treated aluminum nitride filler." The aluminum nitride filler before being surface-treated with the silane coupling agent (SC1) is usually not surface-treated with a silane coupling agent.

[0040] An example of an aluminum nitride filler that has not been surface-treated with a silane coupling agent (hereinafter also referred to as "untreated aluminum nitride filler") is aluminum nitride filler HF-01D (manufactured by Tokuyama Corp.) As the untreated aluminum nitride filler, a commercially available aluminum nitride powder may be used after adjusting the particle size distribution with a sieve and a classifier. The method for producing the untreated aluminum nitride filler is not particularly limited, and aluminum nitride filler produced by a known method can be used. Examples of the method for producing the untreated aluminum nitride filler include a direct nitridation method, a reduction nitridation method, and a gas phase synthesis method.

[0041] The untreated aluminum nitride filler need not have been subjected to a surface treatment with a silane coupling agent, and may have been subjected to a water-resistant treatment, for example, which involves oxidizing the filler surface.

[0042] The silane coupling agent (SC1) is a silane compound having a hydrolyzable group and an organic reactive group containing a (meth)acrylic group, and is preferably an alkoxysilane compound having an organic reactive group containing a (meth)acrylic group.

[0043] The hydrolyzable groups are bonded directly to the silicon atom and include, for example, alkoxy groups such as methoxy and ethoxy groups. The organic reactive group containing a (meth)acrylic group refers to a substituent bonded to a silicon atom that contains a (meth)acrylic group and is other than a hydrolyzable group.

[0044] The (meth)acrylic group is bonded to the silicon atom preferably via a linear, branched or cyclic alkylene group having 1 to 10 carbon atoms. The organic reactive group in the silane coupling agent (SC1) preferably does not contain an amino group of a secondary amine structure.

[0045] Examples of the silane coupling agent (SC1) include 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-acryloxypropyltrimethoxysilane.

[0046] The amount of the silane coupling agent (SC1) used when the untreated aluminum nitride filler is surface-treated with the silane coupling agent (SC1) is preferably 0.1 to 5 parts by mass, more preferably 0.5 to 4 parts by mass, based on 100 parts by mass of the untreated aluminum nitride filler.

[0047] As a method for treating the surface of the untreated aluminum nitride filler with the silane coupling agent (SC1), a known method can be adopted, and either a dry surface treatment method or a wet surface treatment method may be used. Dry surface treatment is a method of dry mixing without using a large amount of solvent when mixing untreated aluminum nitride filler with a silane coupling agent (SC1). Examples of dry surface treatment include a method of gasifying the silane coupling agent (SC1) and mixing it with untreated aluminum nitride filler, a method of spraying or dripping the liquid silane coupling agent (SC1) and mixing it with the untreated aluminum nitride filler, and a method of diluting the silane coupling agent (SC1) with a small amount of organic solvent to increase the amount of liquid, and then spraying or dripping it.

[0048] The wet surface treatment is a method in which a solvent is used when mixing an untreated aluminum nitride filler with a silane coupling agent (SC1). For example, the wet surface treatment may be a method in which an untreated aluminum nitride filler, a silane coupling agent (SC1), and a solvent are mixed, and then the solvent is removed by drying or the like.

[0049] The average particle size D50 of the (B) aluminum nitride filler is preferably 0.2 to 3 μm, and more preferably 0.5 to 1.5 μm. When the average particle size D50 of the (B) aluminum nitride filler is within this range, the resin composition can be easily molded into a film having a thickness of about several μm to several hundred μm, and a cured product made of a film having a thickness within this range tends to have high thermal conductivity. The average particle size D50 in the present invention is the particle size at a cumulative 50% value on a volume basis in the particle size distribution measured by a laser diffraction scattering method. The particle size distribution can be measured by the method described in the Examples section below.

[0050] The maximum particle size Dmax of the (B) aluminum nitride filler is preferably 5 μm or less, more preferably 4.5 μm or less, and even more preferably 4 μm or less. When the maximum particle size Dmax of the (B) aluminum nitride filler is within the above range, the melt viscosity of the resin composition tends to decrease. Therefore, when a film made of the resin composition is heated and pressurized for use in a multilayer printed wiring board and a component-embedded board, the film made of the resin composition has excellent conformability to the shapes of the conductor layer and the cavity.

[0051] The maximum particle size Dmax in the present invention is the maximum particle size (cumulative volume 100% particle size) measured in the particle size distribution measured by a laser diffraction scattering method. The particle size distribution can be measured by the method described in the Examples section below.

[0052] (B) The specific surface area SA of the aluminum nitride filler is preferably 0.5 to 10 m 2 / g, more preferably 0.8 to 7m 2 / g, more preferably 1.0 to 5m 2 When the specific surface area SA of the (B) aluminum nitride filler is within the above range, the (B) aluminum nitride filler has excellent dispersibility in the (A) epoxy resin, and the melt viscosity of the resin composition tends to decrease. The specific surface area SA in the present invention can be measured by the BET method using a flow type automatic specific surface area measuring device, or by the method described in the Examples section below.

[0053] (B) Aluminum nitride filler may contain impurities such as alkaline earth elements and rare earth elements derived from raw materials or intentionally added during the synthesis process, with the upper limit being about 5 parts by mass per 100 parts by mass of (B) aluminum nitride filler. An amount of impurities that significantly reduces the crystallinity of aluminum nitride is not preferable because it causes a decrease in the thermal conductivity of the cured product made of the resin composition. The aluminum nitride content in the (B) aluminum nitride filler is preferably 95 mass % or more, and more preferably 99 mass % or more. The aluminum nitride filler (B) may be of one type or of two or more types.

[0054] [(C) Alumina filler] The resin composition contains (C) an alumina filler. The (C) alumina filler has an average particle diameter D50 (μm) and a specific surface area SA (m 2 The alumina filler (C0) having a product of 2.6 or more and 100% by mass / g (C1) is an alumina filler that has been surface-treated with a silane coupling agent (SC2) having an organic reactive group that includes an amino group of a secondary amine structure, which is different from the organic reactive group possessed by the silane coupling agent (SC1).

[0055] The alumina filler that has been surface-treated with a silane coupling agent (SC2) is also called a "surface-treated alumina filler." (C0) Alumina filler is usually not surface-treated with a silane coupling agent. Alumina filler that is not surface-treated with a silane coupling agent is also called "untreated alumina filler."

[0056] The 10% particle size D10 of the alumina filler (C0) is preferably 0.02 to 1.0 μm, more preferably 0.05 to 0.9 μm, and even more preferably 0.1 to 0.7 μm. The average particle size D50 of the alumina filler (C0) is preferably 0.05 to 1.5 μm, more preferably 0.1 to 1.0 μm, and even more preferably 0.15 to 0.8 μm. The 90% particle size D90 of the alumina filler (C0) is preferably 0.1 to 2.0 μm, more preferably 0.2 to 1.5 μm, and even more preferably 0.3 to 1.0 μm.

[0057] The 10% particle diameter D10 in the present invention is the particle diameter at the cumulative 10% value on a volume basis in the particle size distribution measured by the laser diffraction scattering method. The 90% particle diameter D90 in the present invention is the particle diameter at the cumulative 90% value on a volume basis in the particle size distribution measured by the laser diffraction scattering method. The particle size distribution can be measured by the method described in the Examples section below.

[0058] (C0) The specific surface area SA of the alumina filler is preferably 1 to 50 m 2 / g, more preferably 1.5 to 30m 2 / g, more preferably 2 to 20m 2 / g. (C0) Alumina filler crystallite size L 104 is preferably 20 to 120 nm, more preferably 30 to 100 nm, further preferably 40 to 80 nm, and most preferably 50 to 68 nm. The crystallite size L in the present invention 104 is calculated based on the half-width of the diffraction peak due to the (104) plane obtained from X-ray diffraction measurement by the method described in the Examples section below.

[0059] (C0) Average particle size D50 (μm) and specific surface area SA (m 2 / g) is 2.6 or more, preferably 2.7 or more, more preferably 2.8 or more, and is preferably 10 or less.

[0060] (C0) Average particle size D50 (μm) and crystallite size L 104 (μm) ratio (D50 / L 104 ) is preferably 6.0 or more, more preferably 6.2 or more, and even more preferably 6.4 or more. 104 There is no particular upper limit, but it is generally 20 or less.

[0061] In the (C0) alumina filler, the ratio of the 90% particle size D90 to the 10% particle size D10 (D90 / D10) is preferably 2.3 or less, more preferably 2.1 or less, and even more preferably 2.0 or less. The lower limit of D90 / D10 is not particularly limited as long as it is equal to or greater than 1, which is the theoretical minimum value.

[0062] An example of the (C0) alumina filler having physical property values ​​within the above range is AHPA-0.5AF (manufactured by Sasol).

[0063] It is presumed that the (C0) alumina filler, whose product of average particle diameter D50 and specific surface area SA is within the above range, has a larger specific surface area relative to the particle diameter and has more irregularities on the filler surface than other alumina fillers. Therefore, it is presumed that the (C) alumina filler also has many irregularities on the surface, which reduces the interaction between the (C) alumina fillers, making the (C) alumina filler less likely to aggregate.

[0064] In addition, since the alumina filler (C) is a surface-treated alumina filler that has been surface-treated with a silane coupling agent (SC2) having an amino group with a secondary amine structure, the alumina filler (C) is even less likely to aggregate due to the interaction between the silane coupling agents (SC2), while the affinity between the alumina filler (C) and the epoxy resin (A) is improved. For these reasons, it is presumed that the dispersibility and filling property of the filler are improved, and the fluidity of the resin composition is improved. By improving the filling property of the filler, the filling rate of the filler can be increased, and the thermal conductivity of the cured product made of the resin composition is improved and the linear expansion property is reduced.

[0065] (C0) The large specific surface area relative to the particle size of the alumina filler means that the size of the crystallites that make up the filler particles is small, and D50 / L 104 It is presumed that this is due to the fact that is within the above range. When the specific surface area relative to the particle size of the (C0) alumina filler is large, the particle size distribution of the (C0) alumina filler tends to be narrow and the D90 / D10 tends to be in the above range. In addition to the specific surface area relative to the particle size of the (C0) alumina filler being large, the particle size distribution of the (C0) alumina filler being narrow and the D90 / D10 being in the above range is preferable because it further improves the dispersibility and filling property of the filler.

[0066] When the alumina filler (C0) is surface-treated with a silane coupling agent having an amino group with a primary amine structure, the reactivity between the epoxy resin (A) and the alumina filler becomes excessively high, which may cause the alumina filler to easily aggregate. When the alumina filler (C0) is surface-treated with a silane coupling agent having an amino group with a tertiary amine structure, the reactivity between the epoxy resin (A) and the alumina filler is reduced, and the filling ability of the filler in the resin composition may not be improved.

[0067] Furthermore, it is presumed that if the untreated aluminum nitride filler and the alumina filler (C0) are surface-treated with a silane coupling agent having a different organic reactive group, the interaction between the silane coupling agents of the aluminum nitride filler (B) and the alumina filler (C) can be alleviated, thereby improving the filling ability of the filler and improving the fluidity of the resin composition.

[0068] The silane coupling agent (SC2) is a silane compound having a hydrolyzable group and an organic reactive group containing an amino group of a secondary amine structure, and is preferably an alkoxysilane compound having an organic reactive group containing an amino group of a secondary amine structure. The hydrolyzable groups are bonded directly to the silicon atom and include, for example, alkoxy groups such as methoxy and ethoxy groups.

[0069] The organic reactive group containing an amino group of a secondary amine structure refers to a substituent group containing an amino group of a secondary amine structure and bonded to a silicon atom other than a hydrolyzable group. The amino group of the secondary amine structure is bonded to a silicon atom preferably via a linear, branched or cyclic alkylene group having 1 to 10 carbon atoms. The organic reactive group in the silane coupling agent (SC2) preferably does not contain a (meth)acrylic group.

[0070] An example of the amino group having a secondary amine structure is an amino group represented by -NHR. The R represents an alkyl group or an aryl group. The number of carbon atoms of the alkyl group represented by R is preferably 1 to 30, more preferably 1 to 20, and further preferably 1 to 10. The alkyl group may be linear, branched, or cyclic. The number of carbon atoms of the aryl group represented by R is preferably 6 to 30, more preferably 6 to 20, and further preferably 6 to 10. The amino group of the secondary amine structure is preferably a methylamino group or a phenylamino group, more preferably a phenylamino group. That is, the silane coupling agent (SC2) preferably has an organic reactive group containing a methylamino group or a phenylamino group, more preferably has an organic reactive group containing a phenylamino group.

[0071] Examples of the silane coupling agent (SC2) include N-phenyl-3-aminopropyltrimethoxysilane and 3-(methylamino)propyltrimethoxysilane.

[0072] As the method for surface treatment of the alumina filler (C0) with the silane coupling agent (SC2), any known method can be used without particular limitation, and either a dry surface treatment method or a wet surface treatment method may be used. The amount of the silane coupling agent (SC2) used when the alumina filler (C0) is surface-treated with the silane coupling agent (SC2) is preferably 0.1 to 5 parts by mass, more preferably 0.5 to 4 parts by mass, per 100 parts by mass of the alumina filler (C0).

[0073] The average particle size D50 of the (C) alumina filler is preferably 0.05 to 1.5 μm, more preferably 0.1 to 1.0 μm, and even more preferably 0.15 to 0.8 μm. When the average particle size D50 of the (C) alumina filler is within this range, the resin composition can be easily molded into a film having a thickness of about several μm to several hundred μm, and a cured product made of a film having a thickness within this range tends to have high thermal conductivity.

[0074] The average particle size D50 of the (B) aluminum nitride filler is larger than the average particle size D50 of the (C) alumina filler. When the average particle size D50 of the (B) aluminum nitride filler is larger than the average particle size D50 of the (C) alumina filler, the (C) alumina filler penetrates into the gaps between the (B) aluminum nitride fillers in the resin composition, so that even if the filling rates of the (B) aluminum nitride filler and the (C) alumina filler are increased, the fluidity of the resin composition tends not to decrease excessively. In addition, the contact area of ​​the thermally conductive particles increases, so that the thermal conductivity of the cured product made of the resin composition tends to improve.

[0075] The ratio of the average particle size D50 of the (C) alumina filler to the average particle size D50 of the (B) aluminum nitride filler (average particle size D50 of (C) alumina filler / average particle size D50 of (B) aluminum nitride filler) is preferably 0.02 to 0.9, more preferably 0.05 to 0.8, and even more preferably 0.10 to 0.7. When the ratio of the average particle sizes D50 is within the above range, the (B) aluminum nitride filler and the (C) alumina filler have excellent filling properties in the resin composition, and the melt viscosity of the resin composition tends to decrease.

[0076] The maximum particle size Dmax of the (C) alumina filler is preferably 5 μm or less, more preferably 4 μm or less, and even more preferably 3 μm or less. (C) The specific surface area SA of the alumina filler is preferably 1 to 50 m 2 / g, more preferably 1.5 to 30m 2 / g, more preferably 2 to 20m 2 The alumina filler (C) having a specific surface area SA within the above range has excellent dispersibility in the resin composition, and the melt viscosity of the resin composition tends to be reduced.

[0077] The higher the crystallinity of the (C) alumina filler, the more preferable, and the higher the proportion of alpha crystals in the crystal system, the more preferable. The higher the crystallinity of the (C) alumina filler, the more the thermal conductivity of the cured product made of the resin composition tends to improve. The crystallinity of the (C) alumina filler can be confirmed by X-ray diffraction. The alumina filler (C) may be of one type or of two or more types.

[0078] The resin composition contains 800 to 1800 parts by mass, preferably 1000 to 1600 parts by mass, and more preferably 1100 to 1500 parts by mass of the aluminum nitride filler (B) and the alumina filler (C) relative to 100 parts by mass of the epoxy resin (A). When the total content of the aluminum nitride filler (B) and the alumina filler (C) in the resin composition is within the above range, the resin composition has a good balance of dispersibility and loading property of the filler, as well as flowability, and the cured product has excellent thermal conductivity and linear expansion properties.

[0079] From the viewpoint of dispersibility of the fillers, the ratio of the content of the (B) aluminum nitride filler to the content of the (C) alumina filler ((B) aluminum nitride filler content / (C) alumina filler content) is preferably 95 / 5 to 20 / 80 by mass, more preferably 93 / 7 to 30 / 70, and even more preferably 90 / 10 to 40 / 60.

[0080] [Other ingredients] The resin composition may contain components other than the (A) epoxy resin, the (B) aluminum nitride filler, and the (C) alumina filler (hereinafter also referred to as "other components") within the scope that does not impair the effects of the present invention. Examples of the other components include a curing agent, a curing accelerator, a resin other than the (A) epoxy resin, a filler other than the (B) aluminum nitride filler and the (C) alumina filler, a flame retardant, rubber particles, a thickener, a defoamer, a leveling agent, an adhesion imparting agent, an antioxidant, an ultraviolet degradation inhibitor, and a colorant.

[0081] The curing agent may, for example, be an epoxy resin curing agent. The epoxy resin curing agent has a function of reacting with and curing the reactive epoxy resin when the (A) epoxy resin contains a reactive epoxy resin. By including the epoxy resin curing agent in the resin composition, the cured product obtained by thermally curing the resin composition tends to have high strength and heat resistance.

[0082] As the epoxy resin curing agent, a known curing agent can be used. Examples of the epoxy resin curing agent include phenol-based curing agents, naphthol-based curing agents, active ester-based curing agents, cyanate ester-based curing agents, benzoxazine-based curing agents, and acid anhydride-based curing agents. From the viewpoints of the moldability of the resin composition into a film and the heat resistance of the cured product made of the resin composition, the phenol-based curing agents, naphthol-based curing agents, and active ester-based curing agents are preferred. The curing agents may be used alone or in combination of two or more.

[0083] From the viewpoint of the heat resistance and water resistance of the cured product made of the resin composition, the phenol-based curing agent and naphthol-based curing agent having a novolak structure are preferred. Preferred phenol-based hardeners having a novolac structure include phenol novolac, cresol novolac, bisphenol A-type novolac, phenol aralkyl novolac, biphenyl aralkyl novolac, aminotriazine novolac (phenol novolac containing a triazine structure), triphenylmethane novolac, and cyclopentadiene phenol novolac. As the naphthol-based hardener having a novolak structure, naphthol aralkyl-type phenol novolak, aralkyl-type naphthol-phenol novolak, and naphthol-cresol-type novolak are preferred.

[0084] Examples of phenol-based curing agents and naphthol-based curing agents include "GPH-103", "GPH-65", and "TKG-105" manufactured by Nippon Kayaku Co., Ltd., "TD-2093", "TD-2090", "LF-6161", "LF-4871", "LA-7052", "LA-7054", "LA-1536", and "LA-1356" manufactured by DIC Corporation, "ZX-798" and "SN485" manufactured by Nippon Steel Chemical & Material Co., Ltd., "TPM-100" and "GPNX" manufactured by Gun-ei Chemical Co., Ltd., and "S-TPM" and "J-DDP" manufactured by JFE Chemical Corporation.

[0085] From the viewpoints of moldability of the resin composition into a film and heat resistance of a cured product made of the resin composition, the reactive group equivalent (hydroxyl group equivalent) of the phenol-based curing agent and naphthol-based curing agent is preferably 20 to 4000, more preferably 50 to 2000, and further preferably 50 to 1000. The hydroxyl group equivalent is the mass of the resin per equivalent of hydroxyl group.

[0086] Examples of the active ester curing agent include active ester curing agents having a dicyclopentadiene structure, active ester curing agents having a naphthalene structure, active ester curing agents containing an acetylated product of phenol novolac, and active ester curing agents containing a benzoylated product of phenol novolac. From the viewpoint of the heat resistance and water resistance of the cured product made of the resin composition, the active ester curing agents having a dicyclopentadiene structure and the active ester curing agents having a naphthalene structure are preferred. An example of an active ester-based curing agent having a dicyclopentadiene structure is "HPC-8000-65T" manufactured by DIC Corporation. An example of an active ester-based curing agent having a naphthalene structure is "HPC-8150-62T" manufactured by DIC Corporation.

[0087] From the viewpoints of moldability of the resin composition into a film and heat resistance of a cured product made of the resin composition, the reactive group equivalent (active ester group equivalent) of the active ester curing agent is preferably 50 to 2000, more preferably 50 to 1000, and further preferably 100 to 500. The active ester group equivalent is the mass of resin per equivalent of active ester group.

[0088] The content of the curing agent in the resin composition is preferably 50 to 200 parts by mass, more preferably 65 to 150 parts by mass, and even more preferably 75 to 125 parts by mass, relative to 100 parts by mass of the epoxy resin (A), from the viewpoint of the heat resistance and mechanical strength of the cured product made of the resin composition. The total number of reactive groups such as hydroxyl groups and active ester groups of the curing agent is preferably 0.5 to 2, more preferably 0.6 to 1.5, and even more preferably 0.65 to 1.25, relative to the total number of epoxy groups of the (A) epoxy resin. The total number of epoxy groups of the (A) epoxy resin is the total value of the mass of each epoxy resin divided by the epoxy equivalent for all epoxy resins, and similarly, the total number of reactive groups of the curing agent is the total value of the mass of each curing agent divided by the reactive group equivalent.

[0089] The curing accelerator may be, for example, an epoxy resin curing accelerator. The epoxy resin curing accelerator has a function of accelerating the reaction between the epoxy group of the (A) epoxy resin and the reactive group of the curing agent, and the polymerization of the epoxy group. When the (A) epoxy resin contains a reactive epoxy resin, the resin composition can be easily thermally cured by including the epoxy resin curing accelerator in the resin composition, and the cured product tends to have high strength. The content of the epoxy resin curing accelerator in the resin composition is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, and further preferably 0.1 to 2 parts by mass, based on 100 parts by mass of the epoxy resin (A).

[0090] As the epoxy resin curing accelerator, known substances can be used without particular limitation. For example, amine-based curing accelerators, imidazole-based curing accelerators, phosphorus-based curing accelerators, and guanidine-based curing accelerators can be mentioned, with amine-based curing accelerators and imidazole-based curing accelerators being preferred. The curing accelerators may be used alone or in combination of two or more.

[0091] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene.

[0092] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-phenylimidazole. 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1 ')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-furan Examples of the imidazole compounds include imidazole compounds such as 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins.

[0093] Examples of phosphorus-based curing accelerators include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate.

[0094] Examples of guanidine curing accelerators include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.

[0095] When the resin composition contains a resin other than the (A) epoxy resin (hereinafter, also referred to as "other resin"), the resin composition tends to have excellent flexibility, etc. Therefore, when a film is formed from the resin composition, the film becomes flexible and the winding property is improved, and the impact resistance, etc. of the cured product made of the resin composition is improved, making the cured product less likely to crack.

[0096] Examples of other resins include thermoplastic resins such as phenoxy resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyimide resin, polyamideimide resin, polyethersulfone resin, polyphenylene ether resin, and polysulfone resin. Among these, phenoxy resin, which has a structure similar to that of the epoxy resin (A), is preferred because it has good compatibility with the epoxy resin (A). The other resins may be used alone or in combination of two or more.

[0097] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of a bisphenol A skeleton, a bisphenol F skeleton, a bisphenol S skeleton, a bisphenolacetophenone skeleton, a novolac skeleton, a biphenyl skeleton, a fluorene skeleton, a dicyclopentadiene skeleton, a norbornene skeleton, a naphthalene skeleton, anthracene skeleton, an adamantane skeleton, a terpene skeleton, and a trimethylcyclohexane skeleton. The terminal of the phenoxy resin may have any terminal structure such as a phenolic hydroxyl group or an epoxy group. The phenoxy resin may be used alone or in combination of two or more kinds.

[0098] An example of the phenoxy resin containing a bisphenolacetophenone skeleton is "YX6954BH30" manufactured by Mitsubishi Chemical Corporation. An example of the phenoxy resin containing a bisphenol S skeleton is "YX8100BH30" manufactured by Mitsubishi Chemical Corporation. Further examples of phenoxy resins include "YX7553BH30" manufactured by Mitsubishi Chemical Corporation.

[0099] The weight average molecular weight of the phenoxy resin is preferably 5000 to 10000. The weight average molecular weight of the phenoxy resin is a weight average molecular weight in terms of polystyrene measured by gel permeation chromatography. The content of the other resins such as the phenoxy resin in the resin composition is preferably 0.1 to 50 parts by mass, more preferably 0.5 to 30 parts by mass, and further preferably 1 to 20 parts by mass, relative to 100 parts by mass of the epoxy resin (A).

[0100] (B) Fillers other than aluminum nitride filler and (C) filler of alumina (hereinafter, also referred to as "other fillers") are fillers made of materials other than aluminum nitride and alumina. The other fillers may include, for example, silica, zinc oxide, magnesium oxide, titanium oxide, silicon nitride, boron nitride, aluminum hydroxide, magnesium hydroxide, silicon carbide, calcium carbonate, barium sulfate, talc, and diamond.

[0101] The content of other fillers in the resin composition is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 1 part by mass or less, per 100 parts by mass of the total amount of the (B) aluminum nitride filler and the (C) alumina filler. It is particularly preferable that the resin composition does not contain other fillers. The average particle size D50 of the other fillers is preferably smaller than the average particle size D50 of the aluminum nitride filler (B), more preferably less than 2 μm, and even more preferably less than 1.5 μm. The maximum particle size Dmax of the other fillers is preferably smaller than the maximum particle size Dmax of the aluminum nitride filler (B), more preferably less than 4.5 μm, and even more preferably less than 4 μm.

[0102] The flame retardant imparts flame retardancy to the resin composition when it is used in a semiconductor product. Examples of the flame retardant include organic phosphorus flame retardants, organic nitrogen-containing phosphorus compounds, nitrogen compounds, silicone flame retardants, and metal hydroxides. The flame retardants may be used alone or in combination of two or more.

[0103] When the resin composition contains rubber particles, the internal stress generated when the resin composition is thermally cured is alleviated, and warping of the cured product is reduced, so that the impact resistance of the cured product tends to be excellent. Examples of the rubber particles include fine particles such as core-shell type rubber particles, crosslinked acrylonitrile butadiene rubber particles, crosslinked styrene butadiene rubber particles, and acrylic rubber particles. The average particle size D50 of the rubber particles is preferably 1 μm or less, more preferably 0.8 μm or less.

[0104] The method for producing the resin composition is not particularly limited, and the resin composition can be produced by a known method using a blender, a mixer, or the like, by mixing (A) an epoxy resin, (B) an aluminum nitride filler, (C) an alumina filler, and, as necessary, other components. When mixing, each component may be added to a mixer or the like at the same time and mixed, or each component may be added to a mixer or the like in sequence and mixed. The order of addition when each component is added to a mixer or the like in sequence is not particularly limited. Furthermore, the mixing may be performed under heating, or under a controlled atmosphere such as an inert gas atmosphere, if necessary.

[0105] [Physical properties of resin composition] The resin composition has excellent flowability, and further has excellent linear expansion properties and thermal conductivity after curing.

[0106] Because the resin composition has high fluidity, a film made of the resin composition can conform to the shapes of conductor layers of multilayer printed wiring boards, cavities of component-embedded substrates, and electronic components, thereby improving adhesion between the film made of the resin composition and conductor layers, etc.

[0107] The minimum melt viscosity of the resin composition in the temperature range of 90 to 140° C. is preferably 9000 poise or less, more preferably 6000 poise or less, and is preferably 300 poise or more, more preferably 500 poise or more.

[0108] In the manufacture of a multilayer printed wiring board using a film made of the resin composition, the heat press is usually performed at an appropriate temperature selected within the range of 90 to 140°C. When the minimum melt viscosity is within the above range, the temperature condition for heat-pressing the resin composition for use in a multilayer printed wiring board and a component-embedded substrate can be selected to be close to the temperature at which the melt viscosity is minimum. Therefore, the resin composition can be handled under conditions where the resin composition has high fluidity. The melt viscosity of the resin composition is determined as a complex viscosity by measuring the temperature dispersion of dynamic viscoelasticity using a viscoelasticity measuring device (rotational rheometer).

[0109] The linear expansion coefficient of the cured product of the resin composition is preferably 25 ppm / ° C. or less, and more preferably 22 ppm / ° C. or less. The linear expansion coefficient of the cured product of the resin composition is preferably as close as possible to the linear expansion coefficient of 17 ppm / ° C. of copper, which is the conductor layer. The linear expansion coefficient can be measured using a thermomechanical analyzer, and is determined from the slope of the change in linear expansion rate up to the glass transition temperature.

[0110] The relative density of the resin composition is preferably 0.85 or more, more preferably 0.90 or more, further preferably 0.95 or more, and particularly preferably 0.97 or more. The relative density of the resin composition is expressed as the ratio of the density measured for a cured sample made of the resin composition to the density (theoretical density) calculated from the density and compounding ratio of each component used, and is 1 when the theoretical density and the sample density are the same.

[0111] A high relative density indicates that the filler in the resin composition is highly packed, there are few defects such as voids in the resin composition, and the adhesion at the interface between the components is excellent. Therefore, when the relative density of the resin composition is high, the resin composition has excellent flowability, and the cured product made of the resin composition tends to have excellent thermal conductivity, strength, durability, etc. The upper limit of the relative density is not particularly limited, but is preferably 1.1 or less. The density of the cured product made of the resin composition can be measured by Archimedes' method.

[0112] The thermal conductivity of a cured product of the resin composition is preferably 3.5 W / m·K or more, more preferably 4.0 W / m·K or more, even more preferably 4.5 W / m·K or more, and particularly preferably 5.0 W / m·K or more. When the cured product has high thermal conductivity, a film made of the resin composition can improve the heat dissipation properties of multilayer printed wiring boards and component-embedded boards. The higher the thermal conductivity, the more preferable, but it is generally 30 W / m·K or less. The thermal conductivity can be measured by temperature wave thermal analysis (i-phase method).

[0113] [Applications of resin composition] The resin composition has high fluidity, and the cured product of the resin composition has high thermal conductivity, so that the resin composition can be suitably used as an insulating layer of a multilayer printed wiring board and a sealing resin of a component-embedded board. In addition to these applications, the resin composition can be used in a wide range of applications requiring heat dissipation, such as adhesive films, insulating layers of metal-clad laminates, insulating resin sheets such as prepregs, underfill materials, die bonding materials, semiconductor sealing materials, and hole-filling resins. When the resin composition is used for applications requiring heat dissipation, it is industrially preferable to use the resin composition in the form of a resin composition film obtained by forming the resin composition into a film shape.

[0114] The thickness of the resin composition film is preferably 5 to 250 μm, more preferably 10 to 200 μm, and further preferably 20 to 150 μm.

[0115] The method for producing the resin composition film is not particularly limited, and the resin composition film can be produced by a conventionally known method.As a suitable method for producing the resin composition film, for example, the resin composition is dissolved and mixed in an organic solvent to prepare a varnish, and the varnish is applied on a support using a die coater or the like, and then the varnish is dried by heating and blowing hot air or the like to remove the organic solvent.

[0116] Examples of the organic solvent include acetone, methanol, ethanol, butanol, 2-propanol, 2-methoxyethanol, 2-ethoxyethanol, 1-methoxy-2-propanol, 2-acetoxy-1-methoxypropane, toluene, xylene, methyl ethyl ketone, N,N-dimethylformamide, methyl isobutyl ketone, N-methyl-pyrrolidone, n-hexane, cyclohexane, cyclohexanone, and solvent naphtha, which is a mixture thereof. The organic solvents may be used alone or in combination of two or more kinds.

[0117] From the viewpoint of ease of removal of the organic solvent during drying, the boiling point of the organic solvent is preferably 200° C. or less, more preferably 180° C. or less. The content of the organic solvent in the varnish is not particularly limited and may be appropriately adjusted in consideration of the coatability onto a support, etc.

[0118] The varnish is preferably dried so that the total content of the organic solvent in the resin composition film is preferably 10% by mass or less, more preferably 5% by mass or less. Although it depends on the boiling point of the organic solvent contained in the resin composition film, for example, by heating and drying the varnish at 60°C to 150°C for 1 to 5 minutes, the resin composition film can be obtained which is not excessively heat-cured.

[0119] The resin composition film is preferably in a partially cured state, and is a so-called B-stage film. When the resin composition film is in a partially cured state, the resin composition film is not completely cured, so that the resin composition film can follow the shape of the conductor layer when manufacturing a multilayer printed wiring board and a component-embedded board, and the strength and durability of the resin composition film can be improved by further progressing the curing of the resin composition film thereafter.

[0120] As the support, various plastic films can be suitably used. Examples of plastic films include polyester-based films such as polyethylene terephthalate film, polybutylene terephthalate film, and polyethylene naphthalate, olefin-based films such as polyethylene film and polypropylene film, and polyimide films. Among these, polyethylene terephthalate film is preferred because it has excellent smoothness and heat resistance and is inexpensive.

[0121] From the viewpoints of wettability when applying the resin composition film and releasability when manufacturing various semiconductor substrates, the coated surface of the plastic film serving as the support may be subjected to a release treatment, a matte treatment, a corona discharge treatment, or the like. The support may be a metal foil such as copper foil or aluminum foil. As the copper foil, rolled copper foil, electrolytic copper foil, etc. can be suitably used. By using a metal foil as the support, the process of laminating the metal foil in the production of various substrates can be omitted, and the adhesive strength between the support and the resin composition film can be improved. The thickness of the support is not particularly limited, but is preferably in the range of 5 to 150 μm, more preferably 10 to 100 μm, and further preferably 10 to 60 μm.

[0122] A protective film conforming to the support may be further laminated on the surface of the resin composition film that is not in contact with the support. The thickness of the protective film is not particularly limited, but is, for example, 5 to 40 μm. By laminating a protective film on the surface of the resin composition film that is not in contact with the support, it is possible to prevent the adhesion of dust and the like to the surface of the resin composition film and to prevent scratches, and it is also possible to wind up the resin composition film in a roll. When producing a multilayer printed wiring board, a component-embedded board, and other semiconductor materials, the protective film is peeled off before use.

[0123] The resin composition film has high fluidity and embeddability, and a cured product of the resin composition has high thermal conductivity and a low linear expansion coefficient, and therefore the resin composition film can be suitably used for forming an insulating layer of a multilayer printed wiring board and as a sealing resin for a component-embedded substrate. EXAMPLES

[0124] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0125] The following components were used as materials for the resin composition. <Epoxy resin> (A-1) Solid epoxy resin The following solid epoxy resins were each dissolved in methyl ethyl ketone to prepare a 50% by mass solution. EPPN-501HY (Trisphenolmethane type epoxy resin, manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent 166, softening point 60°C) NC-3000 (biphenyl aralkyl type epoxy resin manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent 276, softening point 58°C) (A-2) Liquid epoxy resin jER828 (Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, epoxy equivalent 189, viscosity (25℃) 135 poise) YDF-8170C (Nippon Steel Chemical & Material Co., Ltd., bisphenol F type epoxy resin, epoxy equivalent 155-165, viscosity 10-15 poise)

[0126] <(B) Aluminum nitride filler> <Untreated aluminum nitride filler> HF-01D (Tokuyama Corporation) (B) Aluminum nitride fillers B-1 to B-5 were prepared by subjecting untreated aluminum nitride fillers to surface treatment with a silane coupling agent (SC1) according to the method described below. Table 1 shows the combination of untreated aluminum nitride filler and silane coupling agent (SC1).

[0127] (B) Method for producing aluminum nitride filler 600 g of untreated aluminum nitride filler, 5 g of a silane coupling agent (SC1), and 1,200 g of isopropyl alcohol were placed in a glass eggplant flask and stirred for 30 minutes with a fluororesin stirring blade. The isopropyl alcohol was then removed under reduced pressure at 50°C using a rotary evaporator, and the mixture was then dried under reduced pressure at 100°C to perform a surface treatment.

[0128] <(C) Alumina filler> (C0) Alumina filler As the (C0) alumina filler, the following untreated alumina filler was used. AHPA-0.5AF (Sasol) ·AA-03F (Sumitomo Chemical Co., Ltd.) NXA-150 (Sumitomo Chemical Co., Ltd.)

[0129] (C) Alumina fillers C-1 to C-7 were prepared by subjecting untreated alumina fillers to surface treatment with a silane coupling agent (SC2) by the following method. Table 2 shows the combination of untreated alumina filler and silane coupling agent (SC2).

[0130] (C) Manufacturing method of alumina filler 600 g of untreated alumina filler, 5 g of silane coupling agent (SC2), and 1200 g of isopropyl alcohol were placed in a glass eggplant flask and stirred for 30 minutes with a fluororesin stirring blade. The isopropyl alcohol was then removed under reduced pressure at 50°C using a rotary evaporator, and the mixture was then dried under reduced pressure at 100°C to perform surface treatment.

[0131] <Silane coupling agent (SC1) and Silane coupling agent (SC2)> N-phenyl-3-aminopropyltrimethoxysilane (KBM-573, Shin-Etsu Chemical Co., Ltd.) 3-Methacryloxypropyltriethoxysilane (KBE-503, manufactured by Shin-Etsu Chemical Co., Ltd.) 3-Acryloxypropyltrimethoxysilane (KBM-5103, Shin-Etsu Chemical Co., Ltd.) 3-(Methylamino)propyltrimethoxysilane (T2868, manufactured by Tokyo Chemical Industry Co., Ltd.) Octyltriethoxysilane (KBE-3083, manufactured by Shin-Etsu Chemical Co., Ltd.) Phenyltrimethoxysilane (KBM-103, manufactured by Shin-Etsu Chemical Co., Ltd.) 3-Aminopropyltrimethoxysilane (KBM-903, Shin-Etsu Chemical Co., Ltd.)

[0132] <Hardening agent> GPH-103 (Nihon Kayaku Co., Ltd., biphenyl aralkylphenol novolac, hydroxyl equivalent 230, softening point 103°C) PHENOLITE TD-2090-60M (DIC Corporation, phenol novolac resin methyl ethyl ketone solution, hydroxyl equivalent 104, solid content 60% by mass) When GPH-103 was used, it was dissolved in methyl ethyl ketone and used as a 50% by mass solution.

[0133] <Phenoxy resin> YX6954BH30 (Mitsubishi Chemical Corporation, bisphenolacetophenone skeleton-containing phenoxy resin, weight average molecular weight 40670, non-volatile content 30% by mass, cyclohexanone / methyl ethyl ketone (1 / 1) solution)

[0134] <Curing accelerator> 4-Dimethylaminopyridine (DMAP, Fujifilm Wako Pure Chemical Industries, Ltd.)

[0135] [Evaluation of filler properties] The physical properties of the untreated alumina filler, (B) the aluminum nitride filler, and (C) the alumina filler were measured under the following conditions. The measurement results are shown in Tables 1 to 3.

[0136] <Average and maximum particle size of filler> Untreated alumina filler, (B) aluminum nitride filler, or (C) alumina filler were added to a dispersion medium to a concentration of 0.2 mass%, and dispersed by irradiating ultrasonic waves of about 200 W for 2 minutes. The particle size distribution of the samples was measured using a laser diffraction scattering type particle size distribution meter (MICROTRACK-MT3300EXII manufactured by Microtrack Bell Co., Ltd.). Water was used as the dispersion medium when dispersing untreated alumina filler, and ethanol was used when dispersing surface-treated aluminum nitride filler and surface-treated alumina filler. In the volume frequency distribution of the particle size obtained (particle size distribution), the volume frequency was accumulated from the smallest particle size, and the particle size at which the cumulative value was 10% was defined as the 10% particle size D10, the particle size at which the cumulative value was 50% was defined as the average particle size D50, the particle size at which the cumulative value was 90% was defined as the 90% particle size D90, and the maximum particle size measured (100% cumulative volume particle size) was defined as the maximum particle size Dmax.

[0137] <Specific surface area of ​​filler> The specific surface areas SA of the untreated alumina filler, (B) aluminum nitride filler, and (C) alumina filler were determined by the BET method (single-point nitrogen adsorption method) using a flow-type automatic specific surface area measuring device (Shimadzu Corporation, Flowsorb II-2300 type). For the measurement, 2 g of powdered untreated alumina filler, (B) aluminum nitride filler, or (C) alumina filler that had been dried at 100°C for 1 hour under a nitrogen gas flow was used.

[0138] <Crystalline size of untreated alumina filler> Using an X-ray diffractometer (Rigaku Corporation, SmartLab), the powder X-ray diffraction profile of the untreated alumina filler was measured under the following conditions: X-ray source: CuKα radiation (wavelength 0.15418 nm), X-ray output: 40 kV-200 mA, 2θ range: 20 to 60°, step width: 0.02°. Based on the half-width of the diffraction peak due to the (104) plane of α-phase alumina obtained around 2θ = 35.1°, the crystallite size was calculated using the Scherrer formula as L 104 The Scherrer constant was set to 0.94.

[0139] <Alpha conversion rate of untreated alumina filler> From the powder X-ray diffraction profile obtained above, the α-phase ratio of the alumina filler was determined by the method described in JP-A-2007-055888. Specifically, the peak height (I 25.6 ) and the peak height of the γ, η, χ, κ, θ or δ phase that appears around 2θ = 46° (I 46 ) and the gelatinization rate was calculated according to the following formula (1). αization rate=I 25.6 / (I 25.6 +I 46 )×100% (1)

[0140] [Table 1]

[0141] [Table 2]

[0142] [Table 3]

[0143] Example 1 50 parts by mass of (A-2) liquid epoxy resin jER828 were blended with 180 parts by mass of a methyl ethyl ketone solution of curing agent GPH-103 (non-volatile content 90 parts by mass), 33 parts by mass of a cyclohexanone / methyl ethyl ketone solution of phenoxy resin YX6954BH30 (non-volatile content 9.9 parts by mass), 0.8 parts by mass of the curing accelerator DMAP, and 270 parts by mass of (C) alumina filler C-1, and the mixture was stirred and mixed. To the above mixture, 100 parts by mass of (A-1) solid epoxy resin EPPN-501HY solution in methyl ethyl ketone (50 parts by mass of non-volatile content), 1,100 parts by mass of (B) aluminum nitride filler B-1, and 300 parts by mass of methyl ethyl ketone were added, and the mixture was stirred for 30 minutes using a homodisper.

[0144] Further, methyl ethyl ketone was appropriately added to adjust the viscosity, and then the mixture was filtered and degassed to prepare a varnish of the resin composition. Next, the varnish of the resin composition was uniformly applied to the release-treated surface of a support (release-treated polyethylene terephthalate film (HY-NS80, manufactured by Higashiyama Film Co., Ltd., thickness 38 μm)) so that the thickness after drying would be 80 μm, and then dried at 80° C. for 3 minutes to produce a resin composition film (B stage).

[0145] [Examples 2 to 12, Comparative Examples 1 to 2, Reference Examples 1 to 8] A resin composition film was produced in the same manner as in Example 1, except that the components of the resin composition were changed as shown in Tables 4-1 and 4-2 (hereinafter collectively referred to as "Table 4").

[0146] [Evaluation of physical properties of resin composition] The physical properties of the resin composition were measured under the following conditions and the results are shown in Table 4.

[0147] <Minimum melt viscosity> The resin composition film was peeled off from the support, and the melt viscosity was measured using a viscoelasticity measuring device (rotational rheometer) (MCR302e manufactured by Anton Paar). The dynamic viscoelasticity was measured under the following conditions: geometry: parallel plates with a diameter of 10 mm, gap: 1 mm, temperature range: 60°C to 180°C, frequency: 1 Hz, strain: 10%, and the minimum value of the complex viscosity in the range of 90 to 140°C was taken as the minimum melt viscosity.

[0148] <Linear expansion coefficient> The resin composition film was cut into a strip of 5 mm width and heat-cured at 180°C for 90 minutes. The obtained cured product was measured twice consecutively by the tensile load method using a thermomechanical analyzer (TMA4000SE manufactured by NETZSCH) in the range of 30°C to 220°C with a sample length (between chucks) of 20 mm, a load of 1 g, and a heating rate of 5°C / min. The linear expansion coefficient was calculated from the slope of the change in linear expansion coefficient from 30°C to the glass transition temperature (the temperature at which the slope of the TMA curve changes) in the second measurement.

[0149] <Thermal conductivity> The resin composition film was heat-treated at 180°C for 90 minutes to be thermally cured. The thermal conductivity (W / m K) of the obtained cured product was 2 / sec) x density (kg / m 3 ) × specific heat (J / kg K). Thermal diffusivity was calculated by averaging 12 measurements taken on the same specimen using temperature wave thermal analysis (ai-Phase Mobile 1u, ISO22007-3, manufactured by ai-Phase Corporation). Density was measured using the Archimedes method (XS204V, manufactured by Mettler Toledo Co., Ltd.), and specific heat was measured using a differential scanning calorimeter (DSC) method (Thermo Plus Evo DSC8230, manufactured by Rigaku Corporation).

[0150] <Relative density> The relative density of the cured material prepared for measuring thermal conductivity was calculated as the ratio of the actual density measured above to the theoretical density calculated by calculation, i.e., actual value / theoretical value. The theoretical density was calculated by setting the density of the aluminum nitride filler (B), the alumina filler (C), and the remaining components excluding the filler components at 3.26 g / m 3 , 3.98g / m 3 , and 1.17 g / m 3 was calculated from the blending ratio of each component.

[0151] [Table 4-1]

[0152] [Table 4-2]

Claims

1. (A) an epoxy resin, (B) an aluminum nitride filler, and (C) an alumina filler, The (B) aluminum nitride filler and the (C) alumina filler are contained in a total amount of 800 to 1800 parts by mass per 100 parts by mass of the (A) epoxy resin, The epoxy resin (A) comprises a solid epoxy resin (A-1) and a liquid epoxy resin (A-2); The aluminum nitride filler (B) is a surface-treated aluminum nitride filler that has been surface-treated with a silane coupling agent (SC1) having an organic reactive group including a (meth)acrylic group, The alumina filler (C) has an average particle diameter D50 (μm) and a specific surface area SA (m 2 the alumina filler (C0) having a product of 2.6 or more and 2.7 g / g is a surface-treated alumina filler that has been surface-treated with a silane coupling agent (SC2) having an organic reactive group containing an amino group of a secondary amine structure, which is different from the organic reactive group of the silane coupling agent (SC1); The average particle size D50 of the aluminum nitride filler (B) is larger than the average particle size D50 of the alumina filler (C); Resin composition.

2. In the (C0) alumina filler, the average particle size D50 (μm) and the crystallite size L calculated from the half-width of the diffraction peak due to the (104) plane obtained by X-ray diffraction measurement 104 (μm) (D50 / L 104 ) is 6.0 or more; The resin composition according to claim 1.

3. In the (C0) alumina filler, the ratio (D90 / D10) of the 90% particle diameter D90 to the 10% particle diameter D10 calculated from the volume-based cumulative particle size distribution is 2.3 or less. The resin composition according to claim 1.

4. The silane coupling agent (SC2) has an organic reactive group including a phenylamino group. The resin composition according to claim 1.

5. The aluminum nitride filler (B) has an average particle size D50 of 0.2 to 3 μm and a maximum particle size Dmax of 5 μm or less, The average particle size D50 of the alumina filler (C) is 0.05 to 1.5 μm. The resin composition according to claim 1.

6. The specific surface area SA of the aluminum nitride filler (B) is 0.5 to 10 m 2 / g, The specific surface area SA of the alumina filler (C) is 1 to 50 m 2 / g, The resin composition according to claim 1.

7. A resin composition film comprising the resin composition according to any one of claims 1 to 6.

8. A multilayer printed wiring board comprising the resin composition according to any one of claims 1 to 6 or a cured product thereof.

9. A component-embedded substrate comprising the resin composition according to any one of claims 1 to 6 or a cured product thereof.

Citation Information

Patent Citations

  • Epoxy resin composition

    JP2011132507A

  • Resin composition

    WO2014208352A1